Marine Oil Spills - Merv Fingas (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Major oil spills attract the attention of the public and the media. This was especially the case after the Deepwater Horizon spill. In recent years, this attention has created a global awareness of the risks of oil spills and the damage they do to the environment. Oil is a necessity in our industrial society, however, and a major component of our lifestyle. This means that the risk of major spills continues as does the interest in spills. The Deepwater Horizon spill began a new series of scientific studies that have greatly increased our understanding of oil spills. This book contains 10 such studies. These studies vary from toxicity studies to social studies of human reaction to spills and risk. Importantly, the book is a sampling of important new topics that have become important after the Deepwater Horizon spill. These new topics include new chemical and tracing techniques, new risk perception techniques, perspectives on human health and spills, and discussion on new fuels. This book makes a significant contribution to the understanding of facets of spills and explores 10 very different facets of oil spills.